Contribution of surgical specialization to improved colorectal cancer survival. Issue 10 (12th August 2013) - Oliphant, R.; Nicholson, G. A.; Horgan, P. G.; Molloy, R. G.; McMillan, D. C.; Morrison, D. S.; ,
Abstract : Background: Reorganization of colorectal cancer services has led to surgery being increasingly, but not exclusively, delivered by specialist surgeons. Outcomes from colorectal cancer surgery have improved, but the exact determinants remain unclear. This study explored the determinants of outcome after colorectal cancer surgery over time. Methods: Postoperative mortality (within 30 days of surgery) and 5‐year relative survival rates for patients in the West of Scotland undergoing surgery for colorectal cancer between 1991 and 1994 were compared with rates for those having surgery between 2001 and 2004. Results: The 1823 patients who had surgery in 2001–2004 were more likely to have had stage I or III tumours, and to have undergone surgery with curative intent than the 1715 patients operated on in 1991–1994. The proportion of patients presenting electively who received surgery by a specialist surgeon increased over time (from 14·9 to 72·8 per cent; P < 0·001). Postoperative mortality increased among patients treated by non‐specialists over time (from 7·4 to 10·3 per cent; P = 0·026). Non‐specialist surgery was associated with an increased risk of postoperative death (adjusted odds ratio 1·72, 95 per cent confidence interval (c.i.) 1·17 to 2·55; P = 0·006) compared with specialist surgery. The 5‐year relative survival rate increased over time and was higher among those treated by specialist compared with non‐specialist surgeons (62·1 versus 53·0 per cent; P < 0·001). Compared with the earlier period, the adjusted relative excess risk ratio for the later period was 0·69 (95 per cent c.i. 0·61 to 0·79; P < 0·001). Increased surgical specialization accounted for 18·9 per cent of the observed survival improvement. Conclusion: Increased surgical specialization contributed significantly to the observed improvement in longer‐term survival following colorectal cancer surgery. Abstract : Makes the case for the specialist